High-proportion reclaimed material low-temperature quick-firing ceramic and preparation method thereof
By mixing the waste generated in the ceramic production process with reinforcement materials, talc and lignin, a high proportion of recycling materials is prepared at low temperature fast-fired ceramics, which solves the problems of resource waste and environmental pollution in the preparation of traditional ceramics, and realizes the ceramics High performance and environmentally friendly preparation.
Patent Information
- Application Number
- CN202411616607.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-13
AI Technical Summary
During the preparation of traditional ceramics, the raw materials consume high, the energy consumption is high and the waste emissions are large, making it difficult to meet the requirements of environmental protection and sustainable development. At the same time, the use of high proportion of recycling materials in ceramics can easily lead to performance degradation.
The preparation method of high proportional recycling materials is adopted to prepare high wear resistance by mixing waste materials (polishing slabs, pressing slabs, and recycling slabs) generated during the ceramic production process with reinforcement materials, talc and lignin. and mechanical properties of ceramics.
It has realized the transformation of waste into treasure, recycling and utilization of unusable raw materials, reducing fuel consumption, and having energy-saving and environmentally friendly effects. At the same time, ceramics have excellent wear resistance and mechanical properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a high-proportion recycled material low-temperature rapid-firing ceramic and a preparation method thereof. Background Art
[0002] The traditional ceramic preparation process consumes a lot of raw materials, consumes a lot of energy, and produces a lot of waste, which does not meet the current requirements of environmental protection and sustainable development. In order to reduce production costs, reduce resource waste and environmental pollution.
[0003] With the increasing amount of industrial waste and recycled materials, how to effectively use recycled materials while ensuring the performance of ceramics has become a hot topic and a difficult problem. The use of high proportions of recycled materials in ceramics can easily lead to performance degradation.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The invention provides a high-proportion recycled material low-temperature rapid-firing ceramic and a preparation method thereof. The ceramic of the invention has excellent wear resistance and mechanical properties.
[0006] The present invention solves the technical problem by adopting the following technical solutions: A high-proportion recycled material low-temperature rapid-fired ceramic, comprising the following raw materials: reinforcing material, polishing clay, pressed clay, talcum clay, recycled material, lignin, and liquid debonding agent; the weight ratio of the reinforcing material, polishing clay, pressed clay, talcum clay, recycled material, lignin, and liquid debonding agent is (1-3): (4-7): (12-18): (1-2): (2-3): (0.05-0.2): (0.8-1.2); The pressed mud comprises the following chemical components in percentage by weight: 18-20% Al 2 O 3 、0.7~1%Fe 2 O 3 , 0.005~0.012%TiO 2 , 2~2.5%MgO, 1.8~2.2%CaO, 3~3.5%K 2 O, 2~2.5%Na 2 O, Remaining SiO 2 .
[0007] The present invention uses waste materials (polishing mud, pressed mud, recycled materials) and reinforcing materials, talcum mud and lignin generated in the ceramic production process to obtain ceramics with excellent wear resistance and mechanical properties. The present invention can turn waste into treasure and recycle unusable raw materials.
[0008] As a preferred embodiment of the present invention, the sintering temperature of the high-proportion recycled material low-temperature rapid-fired ceramic is 1125-1150° C. and the sintering time is 30-60 min.
[0009] The invention adopts low-temperature biscuit firing, has the effect of energy saving and environmental protection, and effectively reduces fuel consumption.
[0010] As a preferred embodiment of the present invention, the recycled material comprises the following chemical components in weight percentage: 15-18% Al 2 O 3 、0.2~0.4%Fe 2 O 3 , 0.08~0.2%TiO 2 , 3~3.5%MgO, 2.5~2.8%CaO, 2.5~2.8%K 2 O, 2.4~2.6%Na 2 O, 5~7% ZnO, balance SiO 2 .
[0011] As a preferred embodiment of the present invention, the polishing mud comprises the following chemical components in weight percentage: 12-14% Al 2 O 3 10~15%B 2 O 3 、0.5~0.8%Fe 2 O 3 , 0.008~0.02%TiO 2 , 4~6%MgO, 2~3%CaO, 3~3.4%K 2 O, 2~3.5%BaO, 1~1.5%Na 2 O, Remaining SiO 2 .
[0012] As a preferred embodiment of the present invention, the reinforcing material includes modified magnesite, calcined kaolin, wollastonite and strontium carbonate; the mass ratio of the modified magnesite, calcined kaolin, wollastonite and strontium carbonate is 1: (0.8~1.2): (0.2~0.5): (0.1~0.4).
[0013] Among them, the modified dolomite of the present invention has excellent reactivity and dispersibility, can prevent the propagation of cracks and increase the bending strength and toughness. After modification, the interface bonding force between the modified dolomite and the ceramic matrix is enhanced, which is helpful for stress transfer and improves the overall mechanical properties of the composite material; the calcined kaolin has a high surface area, which is filled in the ceramic matrix and can effectively improve the density and flexural strength of the ceramic, and the calcined kaolin can form a new reinforcing phase with the alkali metal oxides in the system to improve the sintering and mechanical properties of the ceramic; the needle-shaped crystals of wollastonite play the role of "micro reinforcing ribs" in the ceramic matrix, increase the crack resistance and improve the fracture toughness of the ceramic, and at the specific sintering temperature of the present invention, the wollastonite will partially melt to form a glass phase, which is helpful to improve the density and bonding strength of the ceramic material; strontium carbonate plays the role of a flux in the ceramic, helps to form a low melting point liquid phase during the sintering process, makes the matrix more uniform and dense, and then improves the mechanical properties and sintering density; at the same time, strontium carbonate can refine the grains and inhibit the expansion of cracks to improve the toughness of the ceramic.
[0014] The present invention adopts modified magnesite, calcined kaolin, wollastonite and strontium carbonate as reinforcing materials, which can significantly improve the comprehensive performance of ceramic materials. These reinforcing materials work together to improve the density, toughness and high-temperature stability of the ceramic, reduce crack propagation and thermal expansion mismatch, and improve the mechanical properties and wear resistance of the ceramic. Specifically, the modified magnesite enhances the refractory performance and mechanical stability, the calcined kaolin promotes the formation of mullite and improves the density, the wollastonite improves the crack resistance through its needle-like structure, and the strontium carbonate improves the crack resistance and strength performance through fluxing and grain optimization.
[0015] As a preferred embodiment of the present invention, the preparation method of the modified magnesite is: The magnesite is crushed to 200-500 meshes, and calcined to obtain calcined magnesite powder; Adding calcined magnesite powder and boric acid into the nitric acid solution and stirring evenly to obtain a first mixed solution; Adding vinyl triacetoxysilane, sodium dodecylbenzene sulfonate and graphene to the first mixed solution, stirring evenly, to obtain a second mixed solution; Lanthanum nitrate and cerium nitrate are added to the second mixed solution, subjected to ultrasonic treatment, stirred evenly, filtered, and dried to obtain modified magnesite.
[0016] As a preferred embodiment of the present invention, the calcination temperature is 450-500° C., and the calcination time is 2-5 hours.
[0017] As a preferred embodiment of the present invention, the mass ratio of the calcined magnesite powder, boric acid and nitric acid solution is 1: (0.05-0.12): (8-12); The concentration of the nitric acid solution is 0.5-2 mol / L.
[0018] As a preferred embodiment of the present invention, the mass ratio of the vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, graphene, and the first mixed solution is (0.1-0.3): (0.5-1.2): (1-3): 100; The mass ratio of the lanthanum nitrate, the cerium nitrate and the second mixed solution is (1-3):(1-3):100.
[0019] The present invention also provides a method for preparing a high-proportion recycled material low-temperature rapid-firing ceramic, comprising the following steps: The reinforcing material, polishing mud, pressed mud, talcum mud, recycled material, lignin and liquid debonding agent are mixed evenly, passed through a 200-500 mesh sieve, dried, and pressed under a pressure of 60-100 MPa to obtain a dry blank; the dry blank is sintered, cooled, and edge-grinded to obtain a high-proportion recycled material low-temperature rapid-fired ceramic.
[0020] As a preferred embodiment of the present invention, the sintering temperature is 1125-1150° C. and the sintering time is 30-60 min.
[0021] Beneficial effects of the present invention: The present invention uses waste materials (polishing mud, pressed mud, recycled materials) and reinforcing materials, talcum mud and lignin generated in the ceramic production process to obtain ceramics with excellent wear resistance and mechanical properties. The present invention can turn waste into treasure and recycle unusable raw materials. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0024] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0025] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0026] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained commercially. The raw materials used in the comparative examples and the raw materials used in the parallel experiments of the embodiments are the same commercially available products unless otherwise specified.
[0027] Example 1 A high-proportion recycled material low-temperature rapid-fired ceramic comprises the following preparation raw materials: reinforcing material, polishing clay, pressed clay, talcum clay, recycled material, lignin, and liquid debonding agent; the weight ratio of the reinforcing material, polishing clay, pressed clay, talcum clay, recycled material, lignin, and liquid debonding agent is 2:6:16:1.5:2.5:0.1:0.95.
[0028] Wherein, the liquid dissolving agent is a sodium tripolyphosphate solution with a mass concentration of 20%.
[0029] The pressed mud includes the following chemical components in weight percentage: 18.86% Al 2 O 3 、0.83%Fe 2 O 3 , 0.01%TiO 2 , 2.3%MgO, 1.98%CaO, 3.25%K 2 O, 2.35%Na 2 O, Remaining SiO 2 .
[0030] The recycled material includes the following chemical components in weight percentage: 16.58% Al 2 O 3 、0.24%Fe 2 O 3 、0.15%TiO 2 , 3.35%MgO, 2.67%CaO, 2.72%K 2 O, 2.54%Na 2 O, 6.42% ZnO, balance SiO 2 .
[0031] The polishing mud includes the following chemical components in weight percentage: 12.62% Al 2 O 3 13.51%B 2 O 3 、0.67%Fe 2 O 3 , 0.01%TiO 2 ,5.24%MgO, 2.62%CaO, 3.28%K 2 O, 2.85%BaO, 1.3%Na 2 O, Remaining SiO 2 .
[0032] The reinforcing material comprises modified magnesite, calcined kaolin, wollastonite and strontium carbonate; the mass ratio of the modified magnesite, calcined kaolin, wollastonite and strontium carbonate is 1:1:0.3:0.2.
[0033] The preparation method of the modified magnesite is: The magnesite was crushed to 400 mesh and calcined at 480°C for 3 h to obtain calcined magnesite powder; Add calcined magnesite powder and boric acid to 1 mol / L nitric acid solution, and stir evenly at 100 rpm to obtain a first mixed solution; the mass ratio of the calcined magnesite powder, boric acid, and nitric acid solution is 1:0.1:10; Adding vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, and graphene to the first mixed solution, stirring at a speed of 100 rpm to obtain a second mixed solution; the mass ratio of the vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, graphene, and the first mixed solution is 0.2:1:2:100; Lanthanum nitrate and cerium nitrate are added to the second mixed solution, ultrasonically treated at 300W for 20 minutes, stirred evenly at 100rpm, filtered, and dried to obtain modified magnesite. The mass ratio of the lanthanum nitrate, cerium nitrate, and the second mixed solution is 2:2:100.
[0034] The method for preparing the high-proportion recycled material low-temperature rapid-firing ceramic comprises the following steps: The reinforcing material, polishing mud, pressed mud, talcum mud, recycled material, lignin and liquid debonding agent are mixed evenly, passed through a 400-mesh sieve, dried, and pressed under a pressure of 80 MPa to obtain a dry blank; the dry blank is sintered at 1135°C for 50 minutes, cooled, and edged to obtain a high-proportion recycled material low-temperature rapid-fired ceramic.
[0035] Example 2 A high-proportion recycled material low-temperature rapid-fired ceramic comprises the following preparation raw materials: reinforcing material, polishing clay, pressed clay, talcum clay, recycled material, lignin, and liquid debonding agent; the weight ratio of the reinforcing material, polishing clay, pressed clay, talcum clay, recycled material, lignin, and liquid debonding agent is 1:4:12:1:2:0.05:0.8.
[0036] Wherein, the liquid dissolving agent is a sodium tripolyphosphate solution with a mass concentration of 20%.
[0037] The pressed mud includes the following chemical components in weight percentage: 18.86% Al 2 O 3 、0.83%Fe 2 O 3 , 0.01%TiO 2 , 2.3%MgO, 1.98%CaO, 3.25%K 2 O, 2.35%Na 2 O, Remaining SiO 2 .
[0038] The recycled material includes the following chemical components in weight percentage: 16.58% Al 2 O 3 、0.24%Fe 2 O 3 、0.15%TiO 2 , 3.35%MgO, 2.67%CaO, 2.72%K 2 O, 2.54%Na 2 O, 6.42% ZnO, balance SiO 2 .
[0039] The polishing mud includes the following chemical components in weight percentage: 12.62% Al 2 O 3 13.51%B 2 O 3 、0.67%Fe 2 O 3 , 0.01%TiO 2 ,5.24%MgO, 2.62%CaO, 3.28%K 2 O, 2.85%BaO, 1.3%Na 2 O, Remaining SiO 2 .
[0040] The reinforcing material comprises modified magnesite, calcined kaolin, wollastonite and strontium carbonate; the mass ratio of the modified magnesite, calcined kaolin, wollastonite and strontium carbonate is 1:1:0.3:0.2.
[0041] The preparation method of the modified magnesite is: The magnesite was crushed to 400 mesh and calcined at 480°C for 3 h to obtain calcined magnesite powder; Add calcined magnesite powder and boric acid to 1 mol / L nitric acid solution, and stir evenly at 100 rpm to obtain a first mixed solution; the mass ratio of the calcined magnesite powder, boric acid, and nitric acid solution is 1:0.1:10; Adding vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, and graphene to the first mixed solution, stirring at a speed of 100 rpm to obtain a second mixed solution; the mass ratio of the vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, graphene, and the first mixed solution is 0.2:1:2:100; Lanthanum nitrate and cerium nitrate are added to the second mixed solution, ultrasonically treated at 300W for 20 minutes, stirred evenly at 100rpm, filtered, and dried to obtain modified magnesite. The mass ratio of the lanthanum nitrate, cerium nitrate, and the second mixed solution is 2:2:100.
[0042] The method for preparing the high-proportion recycled material low-temperature rapid-firing ceramic comprises the following steps: The reinforcing material, polishing mud, pressed mud, talcum mud, recycled material, lignin and liquid debonding agent are mixed evenly, passed through a 400-mesh sieve, dried, and pressed under a pressure of 80 MPa to obtain a dry blank; the dry blank is sintered at 1135°C for 50 minutes, cooled, and edged to obtain a high-proportion recycled material low-temperature rapid-fired ceramic.
[0043] Example 3 A high-proportion recycled material low-temperature rapid-firing ceramic comprises the following preparation raw materials: reinforcing material, polishing clay, pressed clay, talcum clay, recycled material, lignin, and liquid debonding agent; the weight ratio of the reinforcing material, polishing clay, pressed clay, talcum clay, recycled material, lignin, and liquid debonding agent is 3:7:18:2:3:0.2:1.2.
[0044] Wherein, the liquid dissolving agent is a sodium tripolyphosphate solution with a mass concentration of 20%.
[0045] The pressed mud includes the following chemical components in weight percentage: 18.86% Al 2 O 3 、0.83%Fe 2 O 3 , 0.01%TiO 2 , 2.3%MgO, 1.98%CaO, 3.25%K 2 O, 2.35%Na 2 O, Remaining SiO 2 .
[0046] The recycled material includes the following chemical components in weight percentage: 16.58% Al 2 O 3 、0.24%Fe 2 O 3 、0.15%TiO 2 , 3.35%MgO, 2.67%CaO, 2.72%K 2 O, 2.54%Na 2 O, 6.42% ZnO, balance SiO 2 .
[0047] The polishing mud includes the following chemical components in weight percentage: 12.62% Al 2 O 3 13.51%B 2 O 3 、0.67%Fe 2 O 3 , 0.01%TiO 2 ,5.24%MgO, 2.62%CaO, 3.28%K 2 O, 2.85%BaO, 1.3%Na 2 O, Remaining SiO 2 .
[0048] The reinforcing material comprises modified magnesite, calcined kaolin, wollastonite and strontium carbonate; the mass ratio of the modified magnesite, calcined kaolin, wollastonite and strontium carbonate is 1:1:0.3:0.2.
[0049] The preparation method of the modified magnesite is: The magnesite was crushed to 400 mesh and calcined at 480°C for 3 h to obtain calcined magnesite powder; Add calcined magnesite powder and boric acid to 1 mol / L nitric acid solution, and stir evenly at 100 rpm to obtain a first mixed solution; the mass ratio of the calcined magnesite powder, boric acid, and nitric acid solution is 1:0.1:10; Adding vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, and graphene to the first mixed solution, stirring at a speed of 100 rpm to obtain a second mixed solution; the mass ratio of the vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, graphene, and the first mixed solution is 0.2:1:2:100; Lanthanum nitrate and cerium nitrate are added to the second mixed solution, ultrasonically treated at 300W for 20 minutes, stirred evenly at 100rpm, filtered, and dried to obtain modified magnesite. The mass ratio of the lanthanum nitrate, cerium nitrate, and the second mixed solution is 2:2:100.
[0050] The method for preparing the high-proportion recycled material low-temperature rapid-firing ceramic comprises the following steps: The reinforcing material, polishing mud, pressed mud, talcum mud, recycled material, lignin and liquid debonding agent are mixed evenly, passed through a 400-mesh sieve, dried, and pressed under a pressure of 80 MPa to obtain a dry blank; the dry blank is sintered at 1135°C for 50 minutes, cooled, and edged to obtain a high-proportion recycled material low-temperature rapid-fired ceramic.
[0051] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not contain reinforcing material, and the other aspects are the same.
[0052] A high-proportion recycled material low-temperature rapid-firing ceramic comprises the following preparation raw materials: polished clay, pressed clay, talcum clay, recycled material, lignin, and a liquid debonding agent; the weight ratio of the polished clay, pressed clay, talcum clay, recycled material, lignin, and the liquid debonding agent is 6:16:1.5:2.5:0.1:0.95.
[0053] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the reinforcing material of Comparative Example 1 is a single modified magnesite, and the other parts are the same.
[0054] The reinforcing material described in this comparative example is modified magnesite.
[0055] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that an equal amount of magnesite is used to replace the modified magnesite in Comparative Example 3, and the other aspects are the same.
[0056] The reinforcing material comprises magnesite, calcined kaolin, wollastonite and strontium carbonate; the mass ratio of the magnesite, calcined kaolin, wollastonite and strontium carbonate is 1:1:0.3:0.2.
[0057] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the preparation method of the modified magnesite described in Comparative Example 4 is different from that in Example 1, and the others are the same.
[0058] The preparation method of the modified magnesite is: The magnesite was crushed to 400 mesh and calcined at 480°C for 3 h to obtain calcined magnesite powder; Add calcined magnesite powder and boric acid to 1 mol / L nitric acid solution, and stir evenly at 100 rpm to obtain a first mixed solution; the mass ratio of the calcined magnesite powder, boric acid, and nitric acid solution is 1:0.1:10; Lanthanum nitrate and cerium nitrate are added to the first mixed solution, ultrasonically treated at 300W for 20 minutes, stirred evenly at 100rpm, filtered, and dried to obtain modified magnesite. The mass ratio of the lanthanum nitrate, cerium nitrate, and the first mixed solution is 2:2:100.
[0059] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the preparation method of the modified magnesite described in Comparative Example 4 is different from that in Example 1, and the others are the same.
[0060] The preparation method of the modified magnesite is: The magnesite was crushed to 400 mesh and calcined at 480°C for 3 h to obtain calcined magnesite powder; Add calcined magnesite powder and boric acid to 1 mol / L nitric acid solution, and stir evenly at 100 rpm to obtain a first mixed solution; the mass ratio of the calcined magnesite powder, boric acid, and nitric acid solution is 1:0.1:10; Add vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, and graphene to the first mixed solution, stir evenly at a speed of 100 rpm to obtain a second mixed solution, filter, and dry to obtain modified magnesite. The mass ratio of vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, graphene, and the first mixed solution is 0.2:1:2:100.
[0061] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the sintering temperature of Comparative Example 6 is 1050° C., and the other aspects are the same.
[0062] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that the sintering temperature of Comparative Example 7 is 1300° C., and the other conditions are the same.
[0063] Test Case 1. The glaze wear resistance was tested using the test method in GB / T3810.7-2016 "Determination of Surface Wear Resistance of Glazed Tiles". The wear loss was tested at 6000 revolutions. The test results are shown in Table 1.
[0064] 2. The flexural strength was tested using a flexural testing machine. The test results are shown in Table 1.
[0065] Table 1
[0066] It can be seen from Table 1 that the ceramics of the present invention have excellent wear resistance and mechanical properties.
[0067] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high proportion of recycled materials and low temperature rapid firing ceramics, characterized in that: The preparation method comprises the following raw materials: reinforcing material, polishing mud, pressed mud, talcum mud, recycled material, lignin, and liquid disintegrating agent; the weight ratio of the reinforcing material, polishing mud, pressed mud, talcum mud, recycled material, lignin, and liquid disintegrating agent is (1-3): (4-7): (12-18): (1-2): (2-3): (0.05-0.2): (0.8-1.2); The squeezed mud includes the following chemical components in weight percentage: 18-20% Al2O3, 0.7-1% Fe2O3, 0.005-0.012% TiO2, 2-2.5% MgO, 1.8-2.2% CaO, 3-3.5% K2O, 2-2.5% Na2O, and the balance SiO2.
2. The high-proportion recycled material low-temperature rapid-firing ceramic according to claim 1, characterized in that: The recycled material includes the following chemical components in weight percentage: 15-18% Al2O3, 0.2-0.4% Fe2O3, 0.08-0.2% TiO2, 3-3.5% MgO, 2.5-2.8% CaO, 2.5-2.8% K2O, 2.4-2.6% Na2O, 5-7% ZnO, and the balance SiO2.
3. The high-proportion recycled material low-temperature rapid-fired ceramic according to claim 1, characterized in that: The polishing mud includes the following chemical components in weight percentage: 12~14% Al2O3, 10~15% B2O3, 0.5~0.8% Fe2O3, 0.008~0.02% TiO2, 4~6% MgO, 2~3% CaO, 3~3.4% K2O, 2~3.5% BaO, 1~1.5% Na2O, and the balance SiO2.
4. The high-proportion recycled material low-temperature rapid-fired ceramic according to claim 1, characterized in that: The reinforcing material comprises modified magnesite, calcined kaolin, wollastonite and strontium carbonate; the mass ratio of the modified magnesite, calcined kaolin, wollastonite and strontium carbonate is 1: (0.8-1.2): (0.2-0.5): (0.1-0.4).
5. The high-proportion recycled material low-temperature rapid-firing ceramic according to claim 4, characterized in that: The preparation method of the modified magnesite is: The magnesite is crushed to 200-500 meshes, and calcined to obtain calcined magnesite powder; Adding calcined magnesite powder and boric acid into the nitric acid solution and stirring evenly to obtain a first mixed solution; Adding vinyl triacetoxysilane, sodium dodecylbenzene sulfonate and graphene to the first mixed solution, stirring evenly, to obtain a second mixed solution; Lanthanum nitrate and cerium nitrate are added to the second mixed solution, subjected to ultrasonic treatment, stirred evenly, filtered, and dried to obtain modified magnesite.
6. The high-proportion recycled material low-temperature rapid-firing ceramic according to claim 5, characterized in that: The calcination temperature is 450-500° C., and the calcination time is 2-5 hours.
7. The high-proportion recycled material low-temperature rapid-firing ceramic according to claim 5, characterized in that: The mass ratio of the calcined magnesite powder, boric acid and nitric acid solution is 1: (0.05-0.12): (8-12); The concentration of the nitric acid solution is 0.5-2 mol / L.
8. The high-proportion recycled material low-temperature rapid-firing ceramic according to claim 5, characterized in that: The mass ratio of the vinyl triacetoxysilane, sodium dodecylbenzene sulfonate, graphene and the first mixed solution is (0.1-0.3): (0.5-1.2): (1-3): 100; The mass ratio of the lanthanum nitrate, the cerium nitrate and the second mixed solution is (1-3):(1-3):
100.
9. The method for preparing a high-proportion recycled material low-temperature rapid-fired ceramic according to any one of claims 1 to 8, characterized in that: The following steps are involved: The reinforcing material, polishing mud, pressed mud, talcum mud, recycled material, lignin and liquid debonding agent are mixed evenly, passed through a 200-500 mesh sieve, dried, and pressed under a pressure of 60-100 MPa to obtain a dry blank; the dry blank is sintered, cooled, and edge-grinded to obtain a high-proportion recycled material low-temperature rapid-fired ceramic.
10. The method for preparing low-temperature rapid-firing ceramics with high proportion of recycled materials according to claim 9, characterized in that: The sintering temperature is 1125-1150° C. and the sintering time is 30-60 min.
Citation Information
Patent Citations
Sepiolite fiber concrete air-entrapping brick with good heat preservation effect
CN103936350A
Silicon nitride combined silicon carbide refractory material and preparation method thereof
CN111439999A
Production process of graphene-containing ceramic
CN111848121A
Antibacterial rock plate and preparation method thereof
CN111995364A
High-skid-resistance transparent dry granules, skid-resistance glaze using same, high-skid-resistance ceramic tile with hydrophobic function and preparation method of high-skid-resistance transparent dry granules
CN116535246A